Pendampingan Implementasi Sistem Administrasi Desa untuk Mewujudkan Smart Village di Pekon Wonodadi Kabupaten Pringsewu Lampung - Didik Kurniawan; Anie Rose Irawati; Dwi Sakethi; Favorisen Rosyking Lumbanraja (Universitas Muhammadiyah Surakarta, 2022)
Conceptually, smart villages are related to resource management carried out by the government by utilizing appropriate technology. There are 3 main elements that make up a smart village that must be accommodated properly, namely government, community and environment. Pekon Wonodadi, Gadingrejo District is one of the leading villages in Pringsewu district, Lampung Province and has good potential in the economic field and has carried out village administration well. This condition makes it possible to transform Wonodadi into a Smart Village so that it can improve village functions and services for the community. One of the obstacles faced by Pekon Wonodadi becoming Smart Village is that the public service administration process is still not integrated into a system, so the services provided are still not optimal in terms of speed and accuracy of data. In addition, there is also a problem in the service file archiving process. In order to make Wonodadi becoming a smart village, mentoring activities and implementation of the Village Service Administration System (SIAP) were carried out where these activities correspond to the 2 elements of smart village, namely the government and the community. Evaluation of the activities was carried out by assessing the level of user acceptance of the SIAP application and it was found that the technology implemented could assist Wonodadi Village in improving the quality of service to the community and in the village administration process. This result is reflected in the survey results where 84% of the people feel that it is easier for them to get village services.